Effect of High Energy Nd:Glass Laser on the Drilled in the 5052 AlMg Alloy - Aljanabi, Khalid M. (Iraqi Journal of Laser, 2020)
This study presents the effect of laser energy on burning loss of magnesium from the holes’ drilled in aluminum alloy 5052. High energy free running pulsed Nd:Glass laser of 300 µs pulse duration has been used to perform the experiments. The laser energy was varied from 1.0 to 8.0 Joules, The drilling processes have been carried out under atmospheric pressure and vacuum inside a specially designed chamber. Microhardness of the blind drilled holes has been investigated .The results indicated that the magnesium loss could be manipulated by adjusting the focusing conditions of the laser beam. Almost, the obtained holes were free of cracks with low taper and low sputter deposition. .The holes performed under atmospheric conditions have higher depth compared to the holes drilled under vacuum.